Cytogenetic Studies in Turkey: Fishes (Vertebrata, Pisces) - Serkan Saygun (Turkish Journal of Bioscience and Collections)
In Turkey surrounded by sea on three sides and hundreds of freshwater resources, it was reported that there is a total of 903 species of fish including freshwater and marine species. In the last thirty-five years in Turkish fish cytogenetics, 103 species/subspecies, 38 of which are endemic species and belonging to more than seventeen orders, corresponding to approximately 11% of the total fish species, had been studied their chromosomes. In all studies, their karyotypes, chromosome number and structure, the arm number (NF), and some specific gene regions (NOR, heterochromatin, etc.) on chromosomes of fish had been revealed by using conventional cytogenetic methods (Giemsa, AgNOR-, C-, GTG-, Q- and RE staining/banding). However, CMA3 and DAPI fluorescence staining in the chromosomes of three species of endemic cyprinids is made for the first time in Turkey. Repetitive DNA and heterochromatic regions in the chromosomes of 48 fish species were determined by NOR and C-banding. Compared to other fish groups in Turkey, the most widely seen Cypriniformes order’s member (from families of Cobitidae, Nemacheilidae, Cyprinidae, and Leuciscidae) is made the cytotaxonomic and cytogenetic analysis of 69 species. According to these results, it was found that mostly chromosome number was 2n = 50 in fishes which were examined cytogenetically. It had also been noted that the highest chromosome number is 2n = 150, and the lowest chromosome number was belonging to a Bagridae species (2n = 32) naturally found in inland waters.